Towards computer-aided reverse engineering of heavy vehicle parts using laser range imaging techniques. (7th October 2004) - Page, D.; Koschan, A.; Sun, Y.; Zhang, Y.; Paik, J.; Abidi, M.
We present an integrated system to automatically generate computer-aided design (CAD) models of existing vehicle parts using laser range imaging techniques. The proposed system integrates data acquisition, model reconstruction, and post processing to generate a set of models from real-world automotive parts. This range image-based, computer-aided reverse engineering (CARE) system has potential for faster model reconstruction over traditional reverse engineering technologies. As part of this system, we also propose a novel crease detection algorithm, which segments the surfaces of reconstructed models along smoothness discontinuities. We present results for both the CARE system and the proposed crease detection algorithm for a set of automotive parts.